A balancing act–finding one´s way to health and well-being: A qualitative analysis of interviews with Swedish university students on lifestyle and behavior change - Katarina Åsberg; Ann Catrine Eldh; Marie Löf; Marcus Bendtsen (PLoS ONE, 2022)
Introduction Unhealthy lifestyle behaviors such as unhealthy diets, low physical activity levels, smoking, and harmful alcohol consumption are common in student populations, which constitute a large group of young adults. As unhealthy lifestyle behaviors are associated with future disease and premature mortality, most commonly from cardiovascular disease and cancers, it is from a public health perspective important to understand such behaviors in young adult populations. The objective of this study was to investigate university students’ experiences of health, health-related behaviors, and the barriers and facilitators for behavior change in terms of health promotion in everyday life. Materials and methods This qualitative study was conducted at a middle-sized university in Sweden. Students represented different faculties and were recruited via non-probability convenience sampling using means such as the snowball technique and social media. The 21 interviews with 24 students, individually or in groups, were transcribed verbatim prior to a qualitative analysis inspired by phenomenological hermeneutics. Results Our interviews showed that university student life is associated with new health-related challenges, for example study-related stress and procrastination implies a lack of energy to engage in healthy routines such as physical activity, and a limited budget affects food choices. While adapting to a new context, students explore personal strategies such as taking on changes in manageable steps, seeking social support, and avoiding disturbances to maintaining health and quality of life. Conclusions Experiences of health while becoming and being a university student can be described as a transition–a balancing act of walking a slack line–during which students seek to manage a healthy balance. In the past, interventions have to some extent been designed to address university students’ behaviors; however, our study aids an understanding of their needs. Future interventions should highlight the transitions they are experiencing and the challenges of student life.